Hubungan Islam dan Yahudi Nasrani dalam Prespektif Hadis - Uccok Kurnia Meliala Hasibuan; Fitriani (Yayasan Sagita Akademia Maju, 2024)
The purpose of this study is to find out Jewish history in a hadith view. In the Bible account, this marks the beginning of Abraham's journey to what is now Can'an, Palestine. The prophet Ya'qub and his sons, who later left Canaan for Egypt, are mentioned in the early history of the Jews, also known as the Children of Israel, in the Qur'an and Hadith. The research methodology used in this study is a qualitative descriptive approach. The research resources used in this procedure come from books, magazines, literature, journals, theses, and primary and secondary data sources. Literary methodology is a method used to obtain data. To draw conclusions from all the research findings, data reduction is the data analysis approach used in this study.the results of the study show that: 1) In history, other names of Jews used throughout history have been Hebrew, Bani Israel, Jew, and Zionist. Nonetheless, there was a difference of opinion about the term